Three-dimensional (3D) Printed Model to Plan the Endoscopic Treatment of Upper Airway Stenosis. Issue 4 (October 2018) - Fiorelli, Alfonso; Scaramuzzi, Roberto; Minerva, Ivana; De Ruberto, Emanuele; Califano, Teresa; Reginelli, Alfonso; Grassi, Roberto; Santini, Mario
Abstract : Background: Endoscopic management of tracheal stenosis may be challenging, especially in the case of complex stenosis placed near the vocal folds, and needing stent placement. Herein, we evaluated the utility of the three-dimensional (3D) airway model for procedural planning in a consecutive series of patients with complex airway stenosis and scheduled for endoscopic treatment. Methods: This strategy was applied to 7 consecutive patients with tracheal stenosis unfit for surgery. The model was printed in a rubber-like material, and almost 7 hours were needed to create it. All patients presented respiratory failure with a mean value of 3.4±0.4 Medical Research Council (MRC) dyspnea scale, 47±3.9 forced expiratory volume in 1 second (FEV1%), and an impairment in the 6-minute walking test (6MWT) (mean value, 175±53 m). The mean length of the stenosis was 19±3.4 mm; 3 of the 7 (43%) patients presented a subglottic stenosis. In 4/7 (57%) patients the stenosis was >5 mm, but its treatment required the placement of a stent because of the presence of tracheal cartilage injury. Results: The mean operation time was 22.7±6.6 minutes. No complications were observed during and after the procedure. A significant increase of MRC (3.4±0.4 vs. 1.6±0.5; P =0.003), of FEV1% (47±3.9 vs. 77±9.7; P =0.001), and of 6MWT (175±53 vs. 423±101; P =0.0002) was observed after the procedure (mean follow-up, 11.1±8.8 mo). Conclusion: Our 3D airway model in the management of airway stenosis is useful for procedural planning, rehearsal, and education. The fidelity level of the 3D model remains the main concern for its wider use in patient care. Thus, our impressions should be confirmed by future prospective studies.